Penguatan Digital Marketing dan Digital Finance pada UMKM Desa Ciawi Bogor - Chandra Ayu Pramestidewi; Ayi Jamaludin Azis; Alfin Adam; Yasmin Nurul Haq (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
MSMEs in Ciawi village generally conduct transactions in their business only relying on simple work and through direct buying and selling transactions and there is no recording system that complies with bookkeeping regulations in accounting or only debit credit, so it is very difficult to know the details of cash in and cash out. The service method used is the ABCD Method (Asset-Based-Community-Driven) by accompanying participants to delve deeper into digital marketing and training MSMEs in cash flow-based bookkeeping, including: cash flow, income statement, capital change report, cost of goods sold, and break event point (BEP) digitally. The results of this digital marketing mentoring and cash flow-based bookkeeping preparation are able to prove that MSMEs in Ciawi village can know the details about digital marketing and digital finance regarding the calculation of financial reports, especially knowing the actual profit and loss report, and cash flow of cash expenditures and cash income.